Synthesis, Characterization and Evaluation of Antioxidant and Antimicrobial activity of Spirochromones Derivatives - Shinde, Achut R.; Muley, Dyanoba B. (Anti-Infective Agents, 2020)
Background: Plethora of literature reported hitherto, depicts impending biological activities for spirochromones. This fact encouraged us for the exploration of the synthesis of new substituted spirochromones and their evaluation of their bioactivities. Objectives: To synthesize different substituted spirochromones derivatives from a spirochromones salt using (R)-pyroglutamic acid as catalyst and their evaluation for antimicrobial and antioxidant activities. Methods: Herein, Aldol cascade method was used for the syntheses of spirochromone derivatives from its salt. A mild protocol is developed for the syntheses of spirochromones derivatives by using (R)-pyroglutamic acid as catalyst. Further, the derivatives and its precursor salt were screened for antimicrobial and antioxidant activity. The antioxidant potentials of the synthesized compounds were checked by DPPH and hydroxyl free radical scavenging assay. Consequently, in vitro antimicrobial activities were performed by well diffusion assay against gram negative bacterium (E. coli) and gram positive bacterium (S. aureus). Results: In the present work, 10 synthesized derivatives are obtained in harmonious yield from a precursor spirochromones salt using (R)-pyroglutamic acid as catalyst. Amongst the studied compounds, 6a depicted maximum antimicrobial activity against the screened microorganisms along with maximum antioxidant activity. Albeit, the synthesized motifs showed moderate to good antioxidant and antimicrobial activities. Conclusion: A mild protocol was developed for the synthesis of spirochromone derivatives from their precursor spirochromones salt by using (R)-pyroglutamic acid as catalyst, which showed moderate to good antimicrobial and antioxidant activity.
Keywords: (R)-pyroglutamic acid